Applying Deep Electrical-Resistivity Tomography Techniques for the Exploration of Medium- and Low-Geothermal Energy Resources - Cristina Sáez Blázquez; Ignacio Martín Nieto; Javier Carrasco; Pedro Carrasco; Daniel Porras; Miguel Ángel Maté-González; Arturo Farfán Martín; Diego González-Aguilera (Energies, 2024)
The growth of the geothermal industry demands the constant search of techniques with the aim of reducing exploration efforts whilst minimizing subsurface uncertainty. The exploration of geothermal resources is fundamental from the exploitation point of view, especially in those regions where this energy is not as widespread as the rest of renewable sources. This research shows how geoelectrical methods can contribute to the investigation and characterization of medium–low enthalpy geothermal resources until about 800 m of depth. A 2000 m long electrical-resistivity tomography profile was performed in a region of Southern Spain with previous evidence of moderate geothermal potential. Results of this geophysical campaign (together with a preliminary geological characterization) allowed for the obtainment of a 2D profile and a pseudo-3D model with extensive information about the subsoil in terms of geological composition and formations. The interpretation of geophysical results denotes the existence of a potential formation constituted by carbonate materials with thickness greater than 300 m, crossing different fractures. Once the ideal location for the geothermal exploitation is defined, the research evaluates the contribution of the possible energy source, deducing that the energy extraction in the potential fracturing area would be double that of the one in the vicinity of the site.